The microgenesis of the watercolor effect - Reeves, Adam; Pinna, Baingio; Roxas, Felix (Frontiers in Psychology, 2013)
The ‘watercolor effect’ is the wash of illusory color that fills in between two enclosing bichromatic contours. We studied the microgenesis of this illusion by varying the duration of the eliciting stimulus (a yellow/purple contour outlining the Mediterranean Sea) and by varying the duration of a blank interval from stimulus offset to an after-coming mask (the ISI). The illusory wash was rated in strength and also matched to a comparison disk of adjustable color but similar luminance. Results indicate that the watercolor effect grows rapidly as stimulus duration is increased to 100 ms and then grows much more slowly. Increasing the ISI beyond 10 ms had no effect, suggesting that the wash arises only during stimulation. Participants who recognized that the bounding contour depicted the Mediterranean reported twice as strong an illusory effect as those who did not, indicating that visual long-term memory modulates the watercolor effect despite the rapidity of its generation.